33. HUMAN RESOURCES AT COMMUNITY HEALTH CENTRE IN LUC NAM DISTRICT, BAC GIANG PROVINCE IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the current situation of human resources at community health centre in Luc Nam district, Bac Giang province in 2023. Methods: The study used a cross-sectional descriptive design, using secondary data. Results: Research shows that in terms of quantity, there are currently 194 people at 25 community health centre in Luc Nam district, but the arrangement is not really suitable to the needs at each community health centre; Human resource structure is unevenly distributed among title, age and gender groups; Human resource quality is relatively good with the rate of medical staffs have college or university degrees is 64,9%, the rate of having good health is 78,9% and the rate of satisfied with work at community health centre is 91,7% Conclusion: The current situation of human resources at community health centre in Luc Nam district is not really suitable in quantity and structure but is of relatively good quality, so there needs to be a solution to arrange and transfer human resources among community health centres to ensure the number and structure of job positions in accordance with the provisions of Circular 03/2023/ TT-BYT.
Keywords: Human resource quality, human resources, community health centre.